2010
DOI: 10.1021/la1001013
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Morphological Characterization of Biopolymer Particles Formed by Electrostatic Complexation of Heat Treated Lactoferrin and Anionic Polysaccharides

Abstract: Biopolymer particles fabricated from proteins and/or polysaccharides can be used to encapsulate functional components or to modify various functional properties of materials. In this study, sub-micrometer biopolymer particles were fabricated by electrostatic complexation of heat-denatured protein (lactoferrin, LF) particles with anionic polysaccharides (alginate, carrageenan, or pectin). The aim of the study was to exploit macromolecular electrostatic interactions to form sub-micrometer sized particles and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 40 publications
10
63
0
Order By: Relevance
“…The main difference between LF and BSA is their isoelectric points. The isoelectric point of LF is between 8 and 9, so this protein exhibits a positive charge at lower pH that decreases continuously and that disappears at the isoelectric point . At higher pH than the isoelectric point, LF is charged negatively.…”
Section: Resultsmentioning
confidence: 99%
“…The main difference between LF and BSA is their isoelectric points. The isoelectric point of LF is between 8 and 9, so this protein exhibits a positive charge at lower pH that decreases continuously and that disappears at the isoelectric point . At higher pH than the isoelectric point, LF is charged negatively.…”
Section: Resultsmentioning
confidence: 99%
“…This showed that encapsulating Lf, especially apo-and native-Lf, in alginate micro-gel particles delays the action of pepsin by limiting its access to Lf thereby leading to lower Lf degradation. The intermolecular interactions which occur between Lf and alginate (Bokkhim et al, 2015;David-Birman, Mackie, & Lesmes, 2013;Peinado et al, 2010) could have played a role in making Lf less available for pepsin degradation. It should be noted that during the gastric digestion, an increase in pH from 2.0 to 3.5 was observed for all types of micro-gel particles.…”
Section: Simulated Gastric Digestionmentioning
confidence: 99%
“…cationic proteins such as Lf) leading to a sustained release of macromolecules from the gel particles Wells & Sheardown, 2007). Research has shown that electrostatic as well as other intermolecular interactions occur between Lf and alginate and that the extent of interactions is affected by the form of Lf (Bokkhim, Bansal, Grøndahl, & Bhandari, 2015;Peinado, Lesmes, Andr es, & McClements, 2010). These interactions minimize the loss of entrapped Lf by diffusion, lower at pH 4 compared to pH 7 for native-and holo-Lf, thus ensuring the stability of Lf within the alginate gel matrix .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the conformational change might also lead to the difference of zeta-potential of LF-coated droplets after the storage at 55 C. The change in the electrical characteristics of the protein upon thermal denaturation might be caused by several factors: protein unfolding leads to exposure of charged groups originally located in the hydrophobic interior; protein aggregation leads to some shielding of charged groups originally located on the hydrophilic exterior; heat treatment may promote chemical degradation of certain charged groups (Peinado, Lesmes, Andres, & McClements, 2010). The conformation change in the LF molecule upon heating, resulted an increase in hydrophobic interactions and disulfide bond formation between LF molecules adsorbed onto different lipid droplets, which may be responsible for the change in zeta-potential of droplets after heating (Tokle et al, 2010).…”
Section: Physical Stabilitymentioning
confidence: 99%